Distribution, Regionalization, and Diversity of the dung beetle genus Phanaeus MacLeay (Coleoptera: Scarabaeidae) using Species Distribution Models - Lizardo, Viridiana; Moctezuma, Victor; Escobar, Federico (Zootaxa, 2022)
The genus Phanaeus is a well-known group whose taxonomy has been described multiple times. Its distribution was previously classified into 11 ecogeographic groups that are equivalent to areas of endemism. Here we use Species Distribution Models to describe species richness patterns. We measured beta-diversity and regionalized its distribution into one region and one transition zone, both with three dominions: Mexican Transition Zone (North American, Mexican, and Mesoamerican dominions) and Neotropical region (Pacific, Brazilian, and Atlantic Forest dominions). We also present a species checklist and updated the distribution maps for 73 of 81 species described so far that reflects all the taxonomical updates. We include a list of all the recorded locations (by country, state, and province), list the recorded habitats and biomes, and describe the modelled environmental conditions for each species.